Revitalizing the Physical Education Social-Justice Agenda in the Global Era: Where Do We Go From Here?. Issue 2 (3rd April 2017) - Azzarito, Laura; Macdonald, Doune; Dagkas, Symeon; Fisette, Jennifer
ABSTRACT: Critical theorists have called attention to the intensification of diversity that is now occurring inside and outside of school, while critically engaging with the detrimental effects of globalization on equity, diversity, and social justice. Globalization presents new challenges to education and to issues of social justice. In this article, we argue that there is a need for scholars in the field of physical education to re-think and re-frame the social-justice agenda to address current inequalities produced by globalization. To support this argument, we first reflect on the impact of global neoliberalism on physical education; second, we discuss the ways in which, as a result of global neoliberalism, public health discourses have an "othering" effect on ethnically diverse young people; third, we propose a theoretical shift from a focus on equality to a focus on difference; and finally, we conclude with considerations for future research and curricula in school physical education.